2015
DOI: 10.1016/j.ajp.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its correlates among undergraduates in Sri Lanka

Abstract: MDD is prevalent in these undergraduates and universities need to develop services to assist them. Such services may also need to focus on supporting those who have experienced threatening life events, particularly those that arise as a result of being an undergraduate, as these may increase the risk of MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 48 publications
6
50
2
Order By: Relevance
“…They indicated that the simultaneity for depression and anxiety may be caused by several factors such as genetic, neurophysiology, neurochemistry, moods and mechanisms of interaction ( 24 , 25 ). In the current study, mental disorder (anxiety and depression) was higher in girls compared to boys and the result was comparable with other studies with almost the same results ( 7 , 8 ). These results were expectable according to the litarature which showed that gender is not a risk factor for depression in childhood, however increasing age and reaching adolescnce can increase depression among females but not in males.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They indicated that the simultaneity for depression and anxiety may be caused by several factors such as genetic, neurophysiology, neurochemistry, moods and mechanisms of interaction ( 24 , 25 ). In the current study, mental disorder (anxiety and depression) was higher in girls compared to boys and the result was comparable with other studies with almost the same results ( 7 , 8 ). These results were expectable according to the litarature which showed that gender is not a risk factor for depression in childhood, however increasing age and reaching adolescnce can increase depression among females but not in males.…”
Section: Discussionsupporting
confidence: 91%
“…Since reaction to stress is related to problem solving disorders, depression and anxiety can cause destruction in social and job performance, and the outcome can have a negative effect on life environment ( 4 , 5 ). Studies show that depression in this period is associated with suicide, drug abuse, acute infectious diseases and low academic performance ( 7 9 ). Therefore, the identification of influenced people and offering the proper interventions is crucial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the need to improve their knowledge about assisting their mentally distressed peers, given the rate of depression among this population [34] and their endorsement of their peers as help-providers when dealing with depression [35]. However, their mean ALGEE score is similar to that obtained by Australian adults [55] and higher than that obtained by adolescents in Australia [43] and Japan [51].…”
Section: Discussionmentioning
confidence: 97%
“…When depression and depression literacy involving the ability to recognise and respond to the disorder were examined among these undergraduates, the findings indicated that although close to 10% could be depressed [34], they may not seek professional assistance for their depression and instead seek informal assistance, such as help from friends [35]. These findings and the limited mental health services available in the country overall [3638], highlight the active role that these undergraduates may play as gateway providers and catalysts in ensuring that their distressed peers get the necessary professional assistance.…”
Section: Introductionmentioning
confidence: 99%